Perancangan Sistem Monitoring dan Pengendalian Budidaya Tanaman Pakcoy Sistem Hidroponik - Ri Munarto; Supriyanto Praptodiyono; Bagus Pratama (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2023)
Urban farming is expected not to require much time to monitor plant growth. Therefor smart agriculture using internet of things should have started to be implemented. In this study the agriculture design hydroponic pakcoy plants, famers from Green village Cilegon city to monitor and control pakcoy plants, replacing the previous manual system. The installation of a microcontroller with the internet of things facility and several sensors for several parameter s of pakcoy plants has been installed in a on-line monitoring dan controlling hydroponic system, namely Wemos Mega 2560, DHT12, Max 6675, PH-4502C, TDS DF Robot Grafity and Ultrasonic HC-SR04 . Data from sensor is monitored and controlled bresult cam be known via smartpohone. The result of the study show that sensors can raplace measuring instrument used in manual farming and control of acidity leveles and nutrition concentarations can be controleed good.